2020
DOI: 10.21203/rs.3.rs-45412/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Burden of Anxiety During the COVID-19 Pandemic Among People Living with HIV (PLHIV) in Pune, India

Abstract: Introduction: There is a dearth of data on anxiety related to the COVID-19 pandemic from people living with HIV (PLHIV). This is a cause of concern as anxiety is associated with antiretroviral therapy (ART) nonadherence. Globally, India has the third largest population of PLHIV and third highest number of COVID-19 cases which are rapidly increasing. Therefore, it is crucial to understand the burden of anxiety and its sources among Asian Indian PLHIV during this pandemic.Methods: We used data from a telephonica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Fifteen studies evaluated mental health outcomes. [81][82][83][84][85] Most (67%) were cross-sectional observational quantitative studies detailing the mental health impact of the pandemic on SGM.…”
Section: Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen studies evaluated mental health outcomes. [81][82][83][84][85] Most (67%) were cross-sectional observational quantitative studies detailing the mental health impact of the pandemic on SGM.…”
Section: Mental Healthmentioning
confidence: 99%
“…Five studies detailed PLHIV. [81][82][83][84][85] A cross-sectional observational quantitative study conducted in Turkey found a relationship between generalised anxiety levels and COVID-19-related anxiety among clinical patients with HIV. 85 A US-based study found that the decision to social distance was associated with COVID-19-related stigma and fears.…”
Section: People With Hivmentioning
confidence: 99%
“…Other cohorts of patients with pre-existing conditions have similarly demonstrated disproportionately high mental health burdens. Marbaniang et al reported that patients with HIV experienced a significantly higher mental burden during the pandemic than non-immunosuppressed patients [22] . These findings support the premise of the study that respondents are aware of the increased risk that their diagnoses pose in developing illness from the COVID-19 virus.…”
Section: Discussionmentioning
confidence: 99%